Presence of bruxism and temporomandibular joint dysfunction during the COVID-19 pandemic: Literature review - Aranha, Rosineide Menezes; Gomes, Maria Francinete de Oliveira; Leal, Lhilandra Thayane Corrêa; Meira, Joyce de Figueiredo; de Souza, Gabriel Catunda; Peres, Silvia Helena de Carvalho Sales; Meira, Gabriela de Figueiredo (Seven Editora, 2023)
The COVID-19 pandemic caused a series of deleterious changes to the health and well-being of the population, the literature points to an increase in cases of bruxism and temporomandibular disorders due to the tension, stress and anxiety experienced during the coronavirus outbreak in the world. Therefore, the objective of this study was to carry out a literature review on the increase in symptoms of temporomandibular disorders (TMD) and bruxism in the population during the pandemic period. Electronic searches were carried out in PubMed, LILACS and the Virtual Health Library (BVS) for articles published between 2019 and December 2022. The pandemic caused an increase in symptoms of stress and anxiety, important factors for a higher prevalence of TMD and bruxism among adolescents and adults. Although these conditions are routinely present in the population, they can lead individuals to pain and disability, so health promotion measures can be used to prepare the population for pandemic episodes.DOI:https://doi.org/10.56238/emerrelcovid19-030